PERKEMBANGAN ILMU PENGETAHUAN PADA PERIODE HARUN AL-RASYID DAN AL-MAKMUN - Nasution, Amhar (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2017)
In some ways the Abbasid Daula has similarities and differences with the Umayyad Daula. As happened in the time of the Umayyad Daula, for example, the nobles Daula Abbasiyah tends to live luxurious and rich in wealth. They love to keep slaves and pet wife (Harem). Life more tends to worldly life than developing Islamic values. But it can not be denied as a khalifah has a high artistic taste and religious obedience. It is no exaggeration to say that the Abbasid Daula experienced a shift in developing government. So it can be classified the period of Abbasid Daula into five periods in connection with the style of government. Meanwhile, according to the origin of the ruler during the period of 508 years Daula Abbasiyah experienced three times the turn of the ruler. That isBani Abbas, Banu Buwaihi, and Bani Saljuk. The fact shows that the period of government was colored by palace intrigue and internal powerstruggle.